Comprehensive Physiology 1995
DOI: 10.1002/cphy.cp110121
|View full text |Cite
|
Sign up to set email alerts
|

Immune System

Abstract: The sections in this article are: T Lymphocyte Subsets Helper ( CD 4) and Cytotoxic ( CD 8) T Cell Subsets Naive and Memory T Cell Subsets Other T Cell Subsets T Lymphocyte Function IL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 267 publications
0
3
0
Order By: Relevance
“…1 and 2). Reports of age-related changes in the absolute and relative proportions of CD4 and CD8 T cells are less consistent (2) but include numerous reports of declines in peripheral blood CD4 percentages in mice (3)(4)(5) and humans (6,7). The proportion of CD4 and CD8 T cells expressing cell surface P-glycoprotein also increases with age in mice (3,8,9).…”
Section: T Cell Subset Patterns That Predict Resistance Tomentioning
confidence: 99%
“…1 and 2). Reports of age-related changes in the absolute and relative proportions of CD4 and CD8 T cells are less consistent (2) but include numerous reports of declines in peripheral blood CD4 percentages in mice (3)(4)(5) and humans (6,7). The proportion of CD4 and CD8 T cells expressing cell surface P-glycoprotein also increases with age in mice (3,8,9).…”
Section: T Cell Subset Patterns That Predict Resistance Tomentioning
confidence: 99%
“…In fact, there have been many studies demonstrating a progressive decrease in the number of T cells with a naive phenotype and a decline in the functions of memory T cells and natural killer (NK) cells [3,4]. A medically relevant deficiency in the immune surveillance system in aged people has been explained by defects in IL-2 production [3], since IL-2 plays an important role in the proliferation and activation of T and NK cells. Thus, analysis of cytokine production is a useful method for studying immune reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, analysis of cytokine production is a useful method for studying immune reactions. Many investigators have reported agerelated changes in production of cytokines in subjects including both genders, although this issue remains controversial [3,5,6].…”
Section: Introductionmentioning
confidence: 99%